ANALISIS SEKTOR EKONOMI UNGGULAN DI KABUPATEN LANDAK - B21109019, Kristian Taedo (Jurnal Pembangunan dan Pemerataan, 2016)
The problems of this research are: 1). What are sectors of the economy into excellent and base sectors in Landak District when viewed through the approach of PDRB in 2010-2014? 2). What is the dominant economic sector at Landak District in 2014, and could be developed in the future? 3). What are the obstacles faced by the government of Landak District in the development of the excelent economic sectors? The data used were secondary data obtained from the Central Bureau of Statistics and the Landak District of West Kalimantan Province. The analysis in this study were using descriptive and qualitative analysis. To assess the economic sectors featured in this area, use location analysis model question (LQ) and analysis model shift Share. Based on the results of data analysis were using the models mentioned above, it is known that the agriculture and plantation sector has a high growth and contribute even more evident in the economic development of Landak District. The Landak district government policies are carried out correctly, as well as taking consideration of the excellent sector or sub sector of the economy that has grown and developed in this area, are expected to further promote regional economic growth so as to realize the higher welfare in Landak District. Keywords: Excelent economic sector, Location Question, Shift Share